PENGARUH KONSENTRASI PUPUK ORGANIK CAIR BioSAR 003 PADA PERTUMBUHAN SELADA (Lactuca sativaL.) DENGAN TEKNIK HIDROPONIK SISTEM WICK SEBAGAI POTENSI PENGEMBANGAN BAHAN AJAR MODUL PEMBELAJARAN IPA SMP - Fajri Cahyadi; Sri Wulandari; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted to determine the effect of concentration liquid organic fertilizer on the growth of lettuce with a wick system engineering and design for the development of science junior high school learning modules in March-May 2016. The study was carried out by two phases: an experiment: the effect of the concentration of liquid organic fertilizer BioSAR 003 on the growth of lettuce (Lactuca sativa L.) with hydroponic techniques wick system and module design phase: analysis of the potential for development teaching materials of science junor high school learning modules, The study used an experimental method by conducting experiments in Greenhouse of Biology Education Laboratory University of Riau, Pekanbaru. Sampling was done by completely randomized design consisting of 4 treatments and 3 replications. The parameters in this study were plant height, leaf number, fresh weight and dry weight of plants. Based on the results of analysis of variance at 5% level, giving the concentration of liquid organic fertilizer BioSAR 003 showed significantly affect the growth of lettuce (Lactuca sativa L.). Liquid organic fertilizer BioSAR 003 with a concentration of 30 cc resulted in the growth of lettuce plants (Lactuca sativa L.) is best reached 18.16 cm high, the number of strands of 9.66 leaves, wet weight of 10.63 g and 0.30 g dry weight. Based on the analysis of the potential of the research results can be used as a module designed development on biotechnology concept for junior high school students.